2006
DOI: 10.1007/s00018-006-6287-0
|View full text |Cite
|
Sign up to set email alerts
|

The semenogelins: proteins with functions beyond reproduction?

Abstract: The coagulum proteins of human semen, semenogelins I and II, are secreted in abundance by the seminal vesicles. Their function in reproduction is poorly understood as they are rapidly degraded in ejaculated semen. However, more recent results indicate that it is time to put the semenogelins in a broader physiological perspective that goes beyond reproduction and fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…In contrast to well-recognized physiologic functions of semenogelins and eppin in the male reproductive system [1][2][3][4][5][6][7], the role of these seminal plasma proteins in human malignancies remains unclear. Only a few studies have shown the expression of semenogelins in malignancies, including lung carcinomas, melanoma, and leukemias [11,12].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In contrast to well-recognized physiologic functions of semenogelins and eppin in the male reproductive system [1][2][3][4][5][6][7], the role of these seminal plasma proteins in human malignancies remains unclear. Only a few studies have shown the expression of semenogelins in malignancies, including lung carcinomas, melanoma, and leukemias [11,12].…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, preoperative serum levels of PSA were significantly higher in patients with n-SgI-positive tumor than in those with n-SgI-negative tumor, suggesting SgI induces PSA secretion from prostate cancer. Because PSA physiologically degrades semenogelins in semen [1,2], it is possible that the increase in PSA levels may, at least partially, represent an attempt to target semenogelins rather than tumor progression.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While semenogelins I and II are considered to be the physiological substrates of PSA [16], [53], several other protein substrates have previously been reported to be degraded by PSA [9]. These proteins or their proteolytic fragments may either promote or inhibit cancer progression, e.g., the cleavage of fibronectin and laminin may be involved in cell invasion [25], [26], IGFBP-3 is associated with cell proliferation [44], [54], galectin-3 is involved in several processes including cell adhesion, proliferation, apoptosis and angiogenesis [55], [56] and plasminogen-derived angiostatin-like fragments inhibit angiogenesis [20].…”
Section: Discussionmentioning
confidence: 99%